Effective Character Education: A Guidebook for Future Educators - Schwartz Merle J (Mc Graw Hill, 2007)
Character education is a national movement encouraging schools to create environments that foster ethical, responsible, and caring young people. It is the intentional, proactive effort by schools, districts, and states to instill in their students important core, ethical values that we all share such as caring, honesty, fairness, responsibility, and respect for self and others. As a part of this movement, Character Education Project is based on research by the nation's leading character education experts published by The Character Education Partnership (CEP). CEP's Eleven Principles of Effective Character Education and Character Education Quality Standards provide guidelines to schools and teachers for the elements needed for effective, comprehensive, and character education. This text is designed to complement those works and provide a tool for future teachers, administrators, and other school personnel.